2006
DOI: 10.1097/01.tp.0000208610.75997.20
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Survival of Microencapsulated Pig Islets and Alginate Biocompatibility in Primates: Proof of Concept

Abstract: Optimal alginate encapsulation significantly prolonged adult pig islet survival into primates for up to 6 months, even in the presence of antibody response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 26 publications
2
144
1
3
Order By: Relevance
“…In this technology, donor islets are coated with a semipermeable membrane that blocks cells and large molecules of the host immune system but is permeable to essential nutrients, glucose, and insulin. Microencapsulation has been shown to be feasible in various experimental systems (14)(15)(16)(17)(18)(19) and in pilot clinical trials (20). However, the limited lifetime of microencapsulated islets and the large islet tissue volume required are obstacles that must be overcome to make this approach clinically viable.…”
mentioning
confidence: 99%
“…In this technology, donor islets are coated with a semipermeable membrane that blocks cells and large molecules of the host immune system but is permeable to essential nutrients, glucose, and insulin. Microencapsulation has been shown to be feasible in various experimental systems (14)(15)(16)(17)(18)(19) and in pilot clinical trials (20). However, the limited lifetime of microencapsulated islets and the large islet tissue volume required are obstacles that must be overcome to make this approach clinically viable.…”
mentioning
confidence: 99%
“…The absence of solid consistent data on glucose metabolism renders these experimental studies difficult to consider as evidence for going to clinical trials. More recently, Gianello and colleagues (16) presented data showing that in nondiabetic primates some of the microencapsulated pig islets survived for up to 6 months and were able to respond in vitro to glucose challenge 135 and 180 days after implantation under the kidney capsula. In addition, the microcapsules were intact under the kidney capsule.…”
Section: Pig-to-primate Preclinical Datamentioning
confidence: 99%
“…Although several chemical formulations of alginate (e.g., high-mannuronic/guluronic and high/low viscosity, with or without additional peptide sequences) have been proposed for islet immunoisolation, high-mannuronic alginate was the most suitable to obtain selective impermeability for molecules over 150 kDa and optimal biocompatibility associated with surrounding angiogenesis and sufficient oxygen tension (up to 40 mmHg) (32). This type of alginate was biocompatible not only in rodents but also into a pig-to-primate model of xenotransplantation for up to 8 months (16,33,34).…”
Section: Biomaterials For Islet Encapsulation Technologymentioning
confidence: 99%
“…In conjunction with this outcome, the same research group discovered that the same graft implanted into diabetic cynomolgus primates resulted in a steady decrease in exogenous insulin requirements for up to 24 weeks post transplantation [ 40 ]. A separate study examined microencapsulated adult porcine islet viability in nondiabetic cynomolgus monkeys and concluded that despite a marked increase in circulating IgM and IgG following implantation as compared with the control group [blank microcapsules], a majority of the grafts were intact, responsive to stimulation by glucose, and free of PFO for up to 6 months post-transplant [ 52 ]. Since anti-porcine antibody levels were higher in the treatment group, it was concluded that some islets were inadequately encapsulated and/or antigenic secretion was occurring.…”
Section: Understanding Xenograft Rejection In Nonhuman Primate Recipimentioning
confidence: 99%
“…The hypothesis of soluble antigen secretion has emerged to explain why intact alginate microcapsules, verifi ably providing complete coverage of the islets via histological/microscopic examination [ 52 ], often failed to fully protect the xenografts from recognition by the adaptive immune system.…”
Section: Porcine Neonatal Pancreatic Cell Clusters [Npccs]mentioning
confidence: 99%